Chemsex and HIV/AIDS: Emerging Trends and Public Health Concerns - Mustafa Khan; Atif Aslam (Indus Journal of Bioscience Research, 2023)
The intersection of chemsex and HIV/AIDS presents a growing public health concern that demands comprehensive exploration. This paper delves into the complex relationship between chemsex practices and the transmission of HIV/AIDS. It provides an in-depth analysis of emerging trends, the socio-cultural context surrounding chemsex, risk factors, and the impact on public health. Additionally, it examines harm reduction strategies, policy implications, and future directions for addressing this multifaceted issue.